A case of hypertrophic cardiomyopathy with right ventricular outflow tract and left midventricular obstruction. Issue 1 (July 2022) - Okada, Natsumi; Shibata, Atsushi; Tanihata, Akiko; Kitada, Ryoko; Ehara, Shoichi; Izumiya, Yasuhiro
Abstract: We describe a case of a 59-year-old woman with hypertrophic cardiomyopathy who remained with right ventricular outflow tract obstruction after the pressure gradient in the left midventricle was resolved by a drug with a negative inotropic effect. The patient was diagnosed with hypertrophic cardiomyopathy 30 years previously and was only on low-dose beta-blocker therapy. She presented at our hospital with suspected exacerbation of heart failure because of the development and exacerbation of dyspnea and chest tightness. Transthoracic echocardiography showed an accelerated blood flow of 3 m/s in the middle of the left ventricle; thus, she was started on cibenzoline, a drug with a negative inotropic effect. After admission, intracardiac pressure measurement showed no pressure gradient in the left chamber. However, there was a pressure gradient of 18 mmHg between the apex of the right ventricle and the right ventricular outflow tract, and right ventricular outflow tract obstruction was confirmed on cardiac magnetic resonance imaging. We decided to reinforce the negative inotropic effect by adding bisoprolol, and the subjective symptoms and auscultatory systolic murmur were eliminated 2 months later. Learning objective: Hypertrophy of the right ventricular myocardium can occur in patients with hypertrophic cardiomyopathy (HCM). However, right ventricular outflow tract obstruction remains a rare finding in patients with HCM, despite the presence of morphological abnormalities such as right ventricular hypertrophy. In patients with HCM, obstruction of the right ventricle should be considered if the symptoms and auscultatory findings do not match the left ventricular imaging findings.